Modified Lemaire lateral tenodesis associated with revision anterior cruciate ligament reconstruction: a case series - Pavão, Douglas Mello; de Faria, José Leonardo Rocha; Albuquerque, Rodrigo Pires e; Moreirão, Marcos de Castro; Vivaqua, Thiago; de Sousa, Eduardo Branco (Brazilian Journal of Case Reports, 2022)
To increase the success and reduce failures related to anterior cruciate ligament reconstruction (ACLR), many techniques of lateral extra-articular tenodesis (LEAT) have been developed, mainly in revision surgeries, where a previous failure has already occurred. This study aims to report a case series of patients with failed ACLR treated with revision techniques combined with LEAT. Seven patients were retrospectively evaluated. At the postoperative analysis, in all patients, after six months of follow-up, there was no range of motion loss, there was an improvement in the functional Lysholm score, a reduction in the instability degree according to the semiological maneuvers of the anterior drawer and in pivot shift tests, compared to preoperative evaluation. No complications were observed. In conclusion, revision ACLR combined with LEAT showed good clinical functional results, without any complications reported.